Performance of an upflow sand filter as a point-of-use treatment system in rural areas - Farhana Abd Lahin; Rosalam Sarbatly; Chiam, Chel Ken (Academy of Sciences Malaysia, 2022)
An upflow sand filter operated in incremental filtration rates (0.072, 0.181, 0.481 m3 m-2 h-1) was studied for turbidity, total suspended solids (TSS), ammonia (NH4), and total coliform removal rates. Each cycle lasted for 45 days. The filter bed was made of sand with 0.10 mm D10 and supported by 0.49 mm and 2.10 mm gravel with a total bed depth of 0.50 m. Turbidity removal was recorded above 80% in all cycles with a maximum concentration of 7.29 NTU. TSS removal was maintained at over 90%, with an average discharge of 4.77 mg/L in all cycles. The NH4 removal increased steadily to 91% for 0.072 m3 m-2 h-1 and 93% for 0.181 m3 m-2 h-1 filtration rate. The algal bloom occurrence at 0.481 m3 m-2 h-1 filtration rate overloaded the system with NH4, declining the removal rate to 45%. Total coliform removal recorded an average of 99% in 0.072 m3 m-2 h-1, 89% in 0.181 m3 m-2 h-1, and 66% in 0.481 m3 m-2 h-1. A high filtration rate resulted in a shorter contact time between pollutants and microorganisms within the filter bed, which reduces the removal efficiency. The Shearing effect was also experienced where the attachments of particles and bacteria were minimised.